2015
DOI: 10.17795/ajcmi-25339
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Antibodies to Hepatitis E Virus Among Pregnant Women

Abstract: Background: Hepatitis E virus (HEV) infection is a major public health problem in developing countries, which could progress to an acute self-limited hepatitis. Young adults and middle-aged people are more likely to be infected than children and elderly persons. The disease is usually mild in general population; severe infection is more seen among pregnant women and leads to a high rate of mortality in this population. Objectives: This study aimed to assess seroprevalence of HEV infection and related risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…Furthermore, we found a significant association between HEV seroprevalence and the number of pregnancy, so that anti-HEV seroprevalence was significantly higher among those women with more than three pregnancies. This finding is consistent with studies done by Mamani et al [ 16 ] and Tabarraei et al [ 17 ], while some other studies do not support this finding [ 14 , 22 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we found a significant association between HEV seroprevalence and the number of pregnancy, so that anti-HEV seroprevalence was significantly higher among those women with more than three pregnancies. This finding is consistent with studies done by Mamani et al [ 16 ] and Tabarraei et al [ 17 ], while some other studies do not support this finding [ 14 , 22 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…HEV seroprevalence of 6.3% reported in the present study is higher than those reported among pregnant women in different parts of Iran, 3.6% in Urmia [ 14 ] and 5.26% in Ahvaz [ 15 ], but lower than those reported in Hamadan (7.4%) [ 16 ] and Gorgan (7.4%) [ 17 ]. Overall, the prevalence of HEV among pregnant women varies from 3.6% to 7.4% in different regions of Iran.…”
Section: Discussioncontrasting
confidence: 78%
“…46 – 48 Compared to the other endemic countries, 50 – 52 the seroprevalence of HEV infection among Iranian pregnant women is low. 45 , 47 , 48 In addition, there is a considerable difference in rate of HEV seroprevalence between Iran and neighbouring countries such as the United Arab Emirates (20.0%) 53 and India (33.67%); 50 meanwhile, it is similar to that reported for Turkey (7.0%). 54…”
Section: Hev In Pregnant Women In Iranmentioning
confidence: 57%
“…Considering the adverse effects of HEV infection on pregnancy outcomes, prevention strategies, appropriate precautions and training programs regarding the possible routes of exposure to HEV as well as routine screening for HEV infection before and during pregnancy are needed to reduce the occurrence and adverse consequences of HEV infection in the pregnant population. 46 , 47 Overall, the importance of HEV infection during pregnancy is underestimated in Iran and there are no current data on the rate of maternal mortality in Iran.…”
Section: Hev In Pregnant Women In Iranmentioning
confidence: 99%
“…After screening by title and abstract, we selected 15 studies for the meta-analysis. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Articles were excluded on the basis of the following: review articles (n=251); book chapters (n=381); topics other than HEV infection in pregnant women such as HEV infection among blood donors, animal studies, duplicate, published before 2015, insufficient information (n=5193); and other languages (n=11) as described in Figure 2. The 15 studies reported on 8337 subjects, of which 1175 subjects were non-pregnant women and were subtracted from the total sample size.…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%